Design of Information Systems in Web-Based Medicine Ordering and Procurement - Vaira, Tischa; Rohmah, Alfiyatu; Zaeniyah, Siti; Pribadi, Prasojo; Santoso, Setiyo Budi (Urecol Journal. Part E: Engineering, 2023)
The drug distribution process determines the sustainability of drug stocks in pharmaceutical services. It is hoped that the design of an information system for drug procurement and ordering can make the distribution process more effective and efficient. While information systems for drug procurement and ordering exist, they are typically designed for individual distributors. This research aims to design an information system by displaying flowcharts that map the drug procurement and ordering process, and by developing user interfaces that facilitate interaction with the system. The research was carried out through a Literature Review. Reference searches were conducted using the Google Scholar search engine. The keywords used in the keyword search were "pharmaceutical wholesalers AND information system design AND drug procurement" and the references selected were within the last 10 years. The information system design was implemented by creating flowchart diagrams using draw.io software and developing user interface designs using Microsoft Office PowerPoint 2019. The drug procurement and ordering information system can be accessed by PBFs as distributors and pharmacists as consumers. The information system designed is included in the e-Health Commerce Application type, which aims to facilitate the payment process and reduce costs incurred by the health environment. The designed information system can create a more efficient drug distribution process.